Rapid evaluation of Farinograph and Extensograph characteristics in bread wheat using near-infrared spectroscopy and chemometrics - Zhao, Zihui; Li, Lei; Li, Wenduan; Tian, Yuanyuan; Zhang, Yan; Zhang, Yong; Ibba, Maria Itria; He, Zhonghu; Hao, Yuanfeng; Tian, Wenfei (Elsevier Ltd., 2025)
Bread wheat (Triticum aestivum L.) plays a vital role in global food security and processing. Understanding the rheological properties of dough is crucial in the food industry and wheat breeding programs to select high-quality varieties. Traditional tests such as Farinograph and Extensograph are essential, but labor-intensive and impractical for high-throughput screening. Near-infrared spectroscopy is a rapid and cost-effective alternative to grain quality assessment. This study aimed to develop calibration models for key rheological properties of dough in wheat using a dataset of 1082 representative samples. Various spectral pre-processing, variable selection, and regression algorithms have been employed for model calibration. The partial least squares regression model for Farinograph water absorption demonstrated strong predictive capabilities (R2c = 0.92, R2v = 0.90, and RPD = 3.20), while qualitative analysis was feasible for other characteristics with high accuracy from 80.23 % to 94.27 %. The developed NIR models provide an efficient method for evaluating wheat quality in food processing and wheat breeding.